Good mine, bad mine: Natural resource heterogeneity and Dutch disease in Indonesia - Paul Pelzl; Steven Poelhekke (Tinbergen Institute, 2018)
We analyse the local effect of exogenous shocks to the value of mineral deposits at the district level in Indonesia using a panel of manufacturing plants. To the best of our knowledge, we are the first to model and estimate the effect of heterogeneity in natural resource extraction methods. We find that in areas where mineral extraction is relatively capital-intensive, mining booms cause virtually no upward pressure on manufacturing earnings per worker, and both producers of traded and local goods benefit from mining booms in terms of employment. In contrast, labour-intensive mining booms drive up local manufacturing wages such that producers of traded goods reduce employment. This source of heterogeneity helps to explain the mixed evidence for `Dutch disease' effects in the literature. In addition, we find no evidence that fiscal revenue sharing between sub-national districts leads to any spillovers.
Keywords: L16; L72; O12; O13; Q30; 330; Dutch disease; natural resources; mining; labour intensity; Indonesia